Β-BaGa4Se7: a promising IR nonlinear optical crystal designed by predictable structural rearrangement. Issue 1 (15th December 2021) - Qian, Zhen; Bian, Qiang; Wu, Hongping; Yu, Hongwei; Lin, Zheshuai; Hu, Zhanggui; Wang, Jiyang; Wu, Yicheng
Abstract : IR NLO crystal β-BaGa4 Se7 was successfully predicted and synthesized. This compound exhibits a strong NLO response, wide transmission range and high laser damage threshold, as well as stable physicochemical properties. Abstract : Rationally designing new inorganic materials with specific functional properties is a fascinating challenge. This is particularly true with the nonlinear optical (NLO) crystals, which can expand the spectral ranges of solid-state lasers from ultraviolet (UV) to infrared (IR) through a second harmonic generation (SHG) or optical parametric oscillation (OPO) process. Herein, a high-performance IR NLO crystal, β-BaGa4 Se7, has been successfully predicted and synthesized by the optimal rearrangement of the NLO-active basic structure units. The stability and functional properties of the material were simulated by first-principles calculations, and eventually it was also successfully synthesized via a high-temperature solid-state reaction in a sealed silica tube. More importantly, this material can exhibit exceedingly excellent NLO properties, including strong SHG response (5 × AgGaS2 ), wide transmission range (0.44–20 μm) and high laser damage threshold (680 MW cm −2, 20 × AgGaS2 ), as well as stable physicochemical properties. These indicate that β-BaGa4 Se7 is a promising IR NLO crystal. The discovery of β-BaGa4 Se7 can also provide new insights into the rational design of IR NLO crystals based on the predictable structural rearrangement.